Multiparametric ultrasound-based assessment of overt hyperthyroid diffuse thyroid disease - Stoian, Dana; Borlea, Andreea; Moisa-Luca, Luciana; Paul, Corina (Frontiers in Endocrinology, 2023)
Hyperthyroidism is a prevalent condition affecting global populations, with an overall prevalence of 1.2%. Our research aimed to establish a systematic diagnostic approach using multiparametric ultrasound (MPUS) to diagnose hyperthyroid diffuse thyroid disease (DTD). We conducted a retrospective study from June 2021 to June 2023 at a specialized endocrinology center in Timisoara, Romania, enrolling subjects presenting with clinical hyperthyroidism. Using the Mach 30 Aixplorer ultrasound equipment, evaluations were performed initially in B-mode US, followed by Color Doppler and Spectral Doppler measurements, and finally, 2D Shear wave elastography (SWE). From the 218 patients analyzed, the diagnosis of DTD with hyperthyroidism was confirmed through biochemical assessment, subgrouping various pathologies such as subacute thyroiditis, Graves' disease, painless thyroiditis, Hashimoto's thyroiditis, iatrogenic, as well as healthy controls. In the first step, B-mode hypoechogenicity had an AUC of 0.951 for DTD detection. In the second step, the peak systolic velocity differentiated Graves' disease with a median of 42.4 cm/s and an AUC of 1. Lastly, the third step consisted of SWE evaluation, revealing a mean elasticity index in the SAT subgroup significantly higher from other subgroups (p<0.001) with an AUC of 1. Our study offers a step-by-step evaluation algorithm for DTD diagnosis, with a very good overall diagnostic performance (AUC of 0.946).